Caledonia the exile of Algerian revolutionaries (1864-1895) - belaidi , Azzedine; larbes, nabila (The Algerian Historical Journal, 2026)
The issue of Algerian exiles in New Caledonia is one of the important historical issues that require further academic study. This makes us wonder about the goal of uprooting the revolutionary Algerians from their land and breaking the blood ties that unite the tribesmen in order to erase the culture by integrating them into a strange society as part of this what we call systematic identity alienation on the part of the French occupier, but on the side of the Algerians, they knew how to defend their identity and their origin and were able to build an environment similar to that of their homeland despite the pain and the suffering, we will therefore try in this article to highlight points on the conditions of Algerian exiles in terms of trial and detention and transportation and stability, that is to say since the beginning of the exile in 1864 until the promulgation of the amnesty decision in 1895.